2021
DOI: 10.1016/j.isci.2021.103296
|View full text |Cite
|
Sign up to set email alerts
|

A nonautophagic role of ATG5 in regulating cell growth by targeting c-Myc for proteasome-mediated degradation

Abstract: Summary Autophagy is a conserved biological process that maintains cell homeostasis by targeting macromolecules for lysosome-mediated degradation. The levels of autophagy are relatively lower under normal conditions than under stress conditions (e.g., starvation), as autophagy is usually stimulated after multiple stresses. However, many autophagy-related regulators are still expressed under normal conditions. Although these regulators have been studied deeply in autophagy regulation, the nonautophag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 38 publications
0
5
0
Order By: Relevance
“…However, the extent to which this is necessary in order to firmly prove causality should not be underestimated. The reason for this is firstly that, as opposed to what was assumed upon their initial identification in the 1990s, most, if not all, ATG proteins have non-autophagic cellular functions ( Yousefi et al, 2006 ; Gan and Guan, 2008 ; Baisamy et al, 2009 ; Hanson et al, 2010 ; DeSelm et al, 2011 ; Chung et al, 2012 ; Lee et al, 2012 ; Velikkakath et al, 2012 ; Maskey et al, 2013 ; Elgendy et al, 2014 ; Rohatgi et al, 2015 ; Chen et al, 2016 ; Joo et al, 2016 ; Joshi et al, 2016 ; Kaizuka and Mizushima, 2016 ; Nunes et al, 2016 ; Yang et al, 2016 ; Guo et al, 2017 ; Ramkumar et al, 2017 ; Wang and Kundu, 2017 ; Cadwell and Debnath, 2018 ; Saleiro et al, 2018 ; Galluzzi and Green, 2019 ; Hu et al, 2020 ; Lindner et al, 2020 ; Wu et al, 2020 ; Fang et al, 2021 ; Li et al, 2021 ; Mailler et al, 2021 ; Nieto-Torres et al, 2021 ; Sun et al, 2021 ; Zhang et al, 2022a ; Hamaoui and Subtil, 2022 ; Rajak et al, 2022 ; Chen et al, 2023 ; Deng et al, 2023 ; Liang et al, 2023 ; Wang et al, 2023 ; Tedesco et al, 2024 ; Tran et al, 2024 ; Yoon et al, 2024 ) that are likely to influence the cellular/phenotypic effects that are observed upon their knockdown, knockout or overexpression, and many of these functions affect pathways that are highly relevant to cancer. Therefore, in order to infer causality, the same cellular/phenotypic effect must be observed upon interference with a number of different ATGs.…”
Section: Discussion—limitations Of Current Studies Main Challenges An...mentioning
confidence: 93%
See 1 more Smart Citation
“…However, the extent to which this is necessary in order to firmly prove causality should not be underestimated. The reason for this is firstly that, as opposed to what was assumed upon their initial identification in the 1990s, most, if not all, ATG proteins have non-autophagic cellular functions ( Yousefi et al, 2006 ; Gan and Guan, 2008 ; Baisamy et al, 2009 ; Hanson et al, 2010 ; DeSelm et al, 2011 ; Chung et al, 2012 ; Lee et al, 2012 ; Velikkakath et al, 2012 ; Maskey et al, 2013 ; Elgendy et al, 2014 ; Rohatgi et al, 2015 ; Chen et al, 2016 ; Joo et al, 2016 ; Joshi et al, 2016 ; Kaizuka and Mizushima, 2016 ; Nunes et al, 2016 ; Yang et al, 2016 ; Guo et al, 2017 ; Ramkumar et al, 2017 ; Wang and Kundu, 2017 ; Cadwell and Debnath, 2018 ; Saleiro et al, 2018 ; Galluzzi and Green, 2019 ; Hu et al, 2020 ; Lindner et al, 2020 ; Wu et al, 2020 ; Fang et al, 2021 ; Li et al, 2021 ; Mailler et al, 2021 ; Nieto-Torres et al, 2021 ; Sun et al, 2021 ; Zhang et al, 2022a ; Hamaoui and Subtil, 2022 ; Rajak et al, 2022 ; Chen et al, 2023 ; Deng et al, 2023 ; Liang et al, 2023 ; Wang et al, 2023 ; Tedesco et al, 2024 ; Tran et al, 2024 ; Yoon et al, 2024 ) that are likely to influence the cellular/phenotypic effects that are observed upon their knockdown, knockout or overexpression, and many of these functions affect pathways that are highly relevant to cancer. Therefore, in order to infer causality, the same cellular/phenotypic effect must be observed upon interference with a number of different ATGs.…”
Section: Discussion—limitations Of Current Studies Main Challenges An...mentioning
confidence: 93%
“…This indicates that loss of autophagy in prostate cancer cells promotes the metastatic process and thus prostate cancer progression. However, since ATG5 has several highly cancer-relevant non-autophagic functions ( Yousefi et al, 2006 ; Maskey et al, 2013 ; Guo et al, 2017 ; Li et al, 2021 ), it will be essential to evaluate whether the increase in migration, invasion and metastasis that was observed upon ATG5 knockdown also occurs upon knockdown of other central ATGs. Moreover, the proposal above is apparently in conflict with the results from another study, which reported that overexpression of wild type HA-tagged ATG5 in DU145 cells, which restored LC3 lipidation, LC3-II flux (as assessed by LC3 WB ± CQ) and LC3 puncta formation, led to enhanced in vitro cell proliferation and migration as assessed by wound healing ( Peng et al, 2021 ).…”
Section: Autophagy In Prostate Carcinogenesismentioning
confidence: 99%
“…Ubiquitin–proteasome system (UPS) is the most important mechanism for regulating Myc protein level ( 33 ). And FBW7 is the best-studied E3 ubiquitin ligase for Myc ( 8 ). Consistently, we found that FBW7 interacted with Myc and mediated EST12-induced K48 ubiquitination and degradation of Myc at late stage ( Figures 6D, F, G ).…”
Section: Discussionmentioning
confidence: 99%
“…Myc is a versatile oncoprotein which regulates cell growth, differentiation, genome instability, apoptosis, etc. ( 8 ). As a prominent oncogene, the Myc target gene network is estimated to comprise about 15% of all genes from flies to humans ( 9 ) and is involved in various physiological functions and clinical diseases including TB.…”
Section: Introductionmentioning
confidence: 99%
“…Autophagy is a conserved process that promotes the intracellular degradation of cytoplasmic proteins or organelles with lysosomes in eukaryotic organisms [ 11 , 12 ]. Under normal conditions, the activity of autophagy is maintained at a relatively low level [ 13 ]. However, upon starvation or other stresses, autophagy is strongly induced [ 14 , 15 ].…”
Section: Introductionmentioning
confidence: 99%